The Adventure of Formative Assessment with Active Feedback in The Vocational Learning: The Empirical Effect for Increasing Students’ Achievement - Waskito; Irzal; Wulansari, Rizky Ema; Kyaw, Zay Ya (Journal of Technical Education and Training, 2022)
The use of formative assessment with active feedback in learning greatly contributes to the professional development of educators and student learning, but the use of the formative function of an evaluation has not been maximally applied in learning. In fact, this formative assessment if applied correctly and with active feedback, it can improve the quality of learning. This formative assessment with active feedback is not only to give a rating, but to see how far the students’ mastery is and what they have not mastered. Many studies explain the positive and negative effects of applying formative tests at various levels and fields of science. Therefore, this study aims to see the impact of the formative assessment with active feedback on vocational education in higher education. This study is a quasi-experimental, with a pretest posttest control design. Based on research findings, the implementation of formative assessment with active feedback has been found to significantly improve students’ academic achievement towards class. The implication of this study is the research findings will contribute to existing knowledge, particularly to determine the effect of formative tests with active feedback on student achievement.